2016
DOI: 10.1093/nar/gkw953
|View full text |Cite
|
Sign up to set email alerts
|

TEtools facilitates big data expression analysis of transposable elements and reveals an antagonism between their activity and that of piRNA genes

Abstract: Over recent decades, substantial efforts have been made to understand the interactions between host genomes and transposable elements (TEs). The impact of TEs on the regulation of host genes is well known, with TEs acting as platforms of regulatory sequences. Nevertheless, due to their repetitive nature it is considerably hard to integrate TE analysis into genome-wide studies. Here, we developed a specific tool for the analysis of TE expression: TEtools. This tool takes into account the TE sequence diversity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
120
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(123 citation statements)
references
References 66 publications
3
120
0
Order By: Relevance
“…Several recent studies have shown that using both uniquely mapped reads and multimapped reads to quantify TEs might introduce biases in expression (Lerat et al 2017;Jin et 22 al. 2015;Criscione et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have shown that using both uniquely mapped reads and multimapped reads to quantify TEs might introduce biases in expression (Lerat et al 2017;Jin et 22 al. 2015;Criscione et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Disentangling epigenetic from genetic variability is becoming easier but remains a very challenging problem, in particular if TEs are accounted for. We envision studies that do a better job of quantifying genome size, the percentage of the genome made up of TEs and the total number of small TE variations (Goubert et al, ; Lerat, Fablet, Modolo, Lopez‐Maestre, & Vieira, ). This could be done by simulating genomes with different TE amounts and using software like dnaPipeTE (Goubert et al, ) for which no reference genome is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Genes with q-values lower than 0.05 and log2FC above 0.5 were considered as differentially expressed. TE differential expression was analyzed using TETOOLs (Lerat et al , 2016).…”
Section: Methodsmentioning
confidence: 99%